Lung Cancer Prevention, Management, and Emerging Therapies - Stewart, David J.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2010)
This comprehensive resource provides authoritative knowledge of the most up-to-date prevention and treatment strategies for thoracic malignancies. Established and investigational therapies are placed in the context of tumor biology for a full understanding of the pharmacogenetics, etiology, and changing epidemiology of lung cancer. Expert clinicians detail the function of predictive and prognostic factors in the utilization of chemo-radiotherapy, adjuvant and neoadjuvant treatment, and targeted agents. The promises and potential pitfalls of investigational strategies are evaluated with exceptional insight and clarity, with unique attention paid to the mechanisms of drug resistance and targets for lung cancer treatment and prevention. Lung Cancer: Prevention, Management, and Emerging Therapies engages the entire spectrum of therapeutic modalities with focus on systemic approaches. Disease coverage includes newly diagnosed and recurrent non-small cell lung cancer, small cell carcinoma, and mesothelioma. Critical examination of the impact, methodology, and design of clinical trials is presented along with new paradigms for personalized approaches and individual risk assessment.
Molecular Pathology of Lung Cancer -- Tumor Microenvironment -- Racial and Ethnic Diversity in Lung Cancer -- Pharmacogenetics of Lung Cancer -- Lung Cancer Prevention -- Adjuvant and Neoadjuvant Therapy of NSCLC -- Chemoradiotherapy for Inoperable Non-small Cell Lung Cancer -- Management of Advanced Non-small Cell Lung Cancer: Front Line Treatment -- Chemotherapy in Previously Treated Patients with Non-small Cell Lung Cancer -- Epidermal Growth Factor Receptor Inhibitors in the Treatment of Non-small Cell Lung Cancer -- Angiogenesis Inhibitors in Lung Cancer -- Other Molecular Targeted Agents in Non-small Cell Lung Cancer -- Vaccine Therapy for Lung Cancer -- Gene-Based Therapies for Lung Cancer -- Lung Cancer Resistance to Chemotherapy -- Small Cell Carcinoma of the Lung -- Mesothelioma -- Advances in Oncology Clinical Research: Statistical and Study Design Methodologies -- Palliative Care for Patients with Lung Cancer -- The Future of Lung Cancer.
Keywords: Medicine; Radiotherapy; Pneumology; Biochemistry; Oncology; Medicine & Public Health; Oncology; Pneumology/Respiratory System; Radiotherapy; Medical Biochemistry